2016
DOI: 10.1093/jjco/hyv214
|View full text |Cite
|
Sign up to set email alerts
|

High expression of long non-coding RNA lncRNA-ATB is correlated with metastases and promotes cell migration and invasion in renal cell carcinoma

Abstract: Objective: To investigate the expression pattern of a novel long non-coding ribonucleic acid activated by transforming growth factor β, long non-coding ribonucleic acid activated by transforming growth factor β, in renal cell carcinoma tissues among the patients with various clinicopathologic features and to detect the possible role of dysregulated long non-coding RNA-ATB in renal cell carcinoma. Methods: The expression of long non-coding ribonucleic acid activated by transforming growth factor β in the renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 20 publications
0
64
0
Order By: Relevance
“…In recent years, lncRNA has become a potential therapy in diagnosing cancer disease, including renal cell carcinoma (RCC), and the biological markers in predicting the prognosis and the treatment for human disease [21]. In this study, we explored the effect of LINC00963 on RIF and OS of CRF through the FoxO signaling pathway, and found that down-regulation of LINC00963 suppressed the RIF and OS of CRF through the activation of the FoxO signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, lncRNA has become a potential therapy in diagnosing cancer disease, including renal cell carcinoma (RCC), and the biological markers in predicting the prognosis and the treatment for human disease [21]. In this study, we explored the effect of LINC00963 on RIF and OS of CRF through the FoxO signaling pathway, and found that down-regulation of LINC00963 suppressed the RIF and OS of CRF through the activation of the FoxO signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RCCRT1 [23], SPRY4-IT1 [24], NBAT-1 [27], MALAT1 [25], and ATB [22] might be used as biomarkers of lymph node metastasis. Although these lncRNAs were associated with the clinicopathological features of patients with RCC; most of these lncRNAs were detected by single study; among these lncRNAs, MALAT1 was the most investigated and reported by two studies; this lncRNA was significantly associated with the tumor stage and lymph node metastasis of patients with RCC after we pooled OR and p -value.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that lncRNAs are involved in the regulation of gene expression, can act as miRNA sponges and scaffolds, and recruit chromatin‐modifying factors to their site of action . LncRNA‐activated by TGF‐β (lncRNA‐ATB) is a long non‐coding RNA that is highly expressed innumerous human cancers, including renal cell carcinoma . A growing number of findings confirmed the existence of a widespread interaction network of competitive endogenous RNAs (ceRNAs), in which lncRNAs may exert functions via targeting miRNAs .…”
mentioning
confidence: 99%
“…14 LncRNA-activated by TGF-β (lncRNA-ATB) is a long non-coding RNA that is highly expressed innumerous human cancers, 15,16 including renal cell carcinoma. 17 A growing number of findings confirmed the existence of a widespread interaction network of competitive endogenous RNAs (ceRNAs), in which lncRNAs may exert functions via targeting miRNAs. 18 Similarly, lncRNA-ATB has been reported to promote the invasionmetastasis cascade and regulate EMT in HCC via negative modulation of miR-200 family, upregulating ZEB1, ZEB2 and suppressing E-cadherin (E-cad) expression.…”
mentioning
confidence: 99%